JOURNALISTS OR INFLUENCERS? THE APPROPRIATION OF DIGITAL INFLUENCERS PRACTICES AS A TOOL OF JOURNALISTIC VALUE - Karhawi, Issaaf; Camargo, Isadora Ortiz de (Brazilian Creative Industries Journal, 2023)
This article answers two main questions: What are the similarities and differences between journalists’ online practices and that of digital influencers’? How have social media and the intimate perspective shortened the distances between journalists and their audience? To understand this scenario, a trio of Brazilian television journalists was investigated to comprehend their digital presence. The authors elaborated an exploratory methodology for qualitative analysis of Instagram publications. Based on elements that characterize the digital influencers and journalistic practices, a score was also created to understand the potentials of their discourse, performances and content strategies online.